Managing the industrial enterprises development in ecosystem interaction - O. E. Astafyeva (Вестник университета, 2022)
The article considers a new approach to managing the development of enterprises operating in a period of digital transformations and ecosystem interaction. The concepts of sustainability and development in an economic context have been analysed. The author’s interpretation of the concept of sustainable development has been outlined and the factors that ensure the development and sustainability of enterprises have been identified. The benefits and limitations of sustainable development management, and the specific of data analysis in the digital ecosystem of the industrial enterprise as a component of sustainability and security of actors, have been defined. The components of a sustainable development framework have been identified and the effects obtained at the ecosystem level of interaction have been highlighted. Guidelines for new management approaches to the organisation of modern business processes and management decisions have been given.